2014
DOI: 10.1039/c3cp54570a
|View full text |Cite|
|
Sign up to set email alerts
|

Size and shape dependent photoluminescence and excited state decay rates of diamondoids

Abstract: We present photoluminescence spectra and excited state decay rates of a series of diamondoids, which represent molecular structural analogues to hydrogen-passivated bulk diamond. Specific isomers of the five smallest diamondoids (adamantane-pentamantane) have been brought into the gas phase and irradiated with synchrotron radiation. All investigated compounds show intrinsic photoluminescence in the ultraviolet spectral region. The emission spectra exhibit pronounced vibrational fine structure which is analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 41 publications
4
54
0
Order By: Relevance
“…25,29,45 In a previous study, we have already shown that based on the calculation of vibrationally resolved FranckCondon spectra in the frame of the TDDFT method, which includes the structural displacements upon changing the electronic state, the experimental emission spectrum of adamantane can be accurately reproduced. 28 Here, we have further exploited this approach and have obtained a very good agreement of the calculated vibrationally resolved spectra with their measured high-resolution counterparts for a large class of higher diamondoids. A thorough Franck-Condon analysis, including Herzberg-Teller coupling if necessary, has provided a detailed understanding of the form and composition of the spectral features.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…25,29,45 In a previous study, we have already shown that based on the calculation of vibrationally resolved FranckCondon spectra in the frame of the TDDFT method, which includes the structural displacements upon changing the electronic state, the experimental emission spectrum of adamantane can be accurately reproduced. 28 Here, we have further exploited this approach and have obtained a very good agreement of the calculated vibrationally resolved spectra with their measured high-resolution counterparts for a large class of higher diamondoids. A thorough Franck-Condon analysis, including Herzberg-Teller coupling if necessary, has provided a detailed understanding of the form and composition of the spectral features.…”
Section: Resultsmentioning
confidence: 98%
“…The frequencies closely match the results of the Raman measurements reported by Filik et al 17 Previous calculations for adamantane have shown that the tetrahedral symmetry exhibited in the electronic ground state is reduced in the electronically excited state. 28 Similarly, for triamantane, a change in the molecular geometry after excitation is observed, and the calculated excited state structure shows no symmetry. 15,24 The absorption spectrum thus shows a smooth onset with the optical gap value of 6.10 eV.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape and the size of these micro/nanostructures precisely lie at the heart of the physical and chemical properties of the functional micro/nanomaterials10111213141516. In recent decades, tremendous efforts have been made towards the development of synthetic procedures for inorganic compounds, such as Ag, Pd, and ZnO171819.…”
mentioning
confidence: 99%